Spatial analysis of female intentional homicides* - Barros, Sheyla Carvalho de; Oliveira, Conceição Maria de; Silva, Amanda Priscila de Santana Cabral; Melo, Marcella Fernandes de Oliveira; Pimentel, Dayane da Rocha; Bonfim, Cristine Vieira do (Revista da Escola de Enfermagem da USP, 2021)
Objective: To analyze the characteristics and spatial distribution of female intentional homicides, according to the regional health offices, in a state in the Northeast Region of Brazil. Method: This is an ecological study that had the municipality and regional health offices as units of analysis and used data from the Brazilian Mortality Information System. Mortality rates were calculated and smoothed by the local empirical Bayesian method. To identify the existence of spatial autocorrelation, the Moran’s index was used. Results: A total of 1,144 homicides were reported, with an average rate of 6.2/100,000 women. For all regional health offices, the 10-39 age group, black race/skin color, and single marital status prevailed. The homicides took place in public spaces. The days of the week with the highest records were Saturday and Sunday and the months of the year December, January, February, and June. The global Moran’s index was 0.6 (p = 0.01). Clusters of municipalities with high homicide rates were identified in regional health offices III and IV. Conclusions: The homicide victims were young, black, and single. The spatial analysis found critical areas of homicide occurrence, which are a priority for actions to prevent violence against women.